2019
DOI: 10.3390/diseases7010015
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Intertwines with Different Diseases—Recent Strategies for Therapeutic Approaches

Abstract: Autophagy is a regular and substantial “clear-out process” that occurs within the cell and that gets rid of debris that accumulates in membrane-enclosed vacuoles by using enzyme-rich lysosomes, which are filled with acids that degrade the contents of the vacuoles. This machinery is well-connected with many prevalent diseases, including cancer, HIV, and Parkinson’s disease. Considering that autophagy is well-known for its significant connections with a number of well-known fatal diseases, a thorough knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 224 publications
(261 reference statements)
0
13
0
Order By: Relevance
“…Increasing evidence has shown that targeting ROS/NADPH oxidase, NLRP3 inflammasome, MAPK/NF-κB signaling, Nrf2 signaling, autophagy, and mitochondrial bioenergetics provides potential therapeutic strategies for the prevention and treatment of various inflammatory diseases [ 15 , 137 , 138 , 139 , 140 , 141 , 142 ]. However, given the multifactorial etiology of inflammatory diseases and the limited success of antioxidant therapies achieved to date, therapeutic targets at single risk factor interventions are not enough to block the progression of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that targeting ROS/NADPH oxidase, NLRP3 inflammasome, MAPK/NF-κB signaling, Nrf2 signaling, autophagy, and mitochondrial bioenergetics provides potential therapeutic strategies for the prevention and treatment of various inflammatory diseases [ 15 , 137 , 138 , 139 , 140 , 141 , 142 ]. However, given the multifactorial etiology of inflammatory diseases and the limited success of antioxidant therapies achieved to date, therapeutic targets at single risk factor interventions are not enough to block the progression of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…About 5–10% of PD cases have Mendelian inheritance [21,22]. There are about 20 genes with the mutations that are known to be responsible for disturbances in the cellular processes leading to neuronal death in SNpc, including mitochondrial dysfunction, defects in mitoautophagy and chaperone-mediated autophagy, defective dopamine metabolism, endoplasmic reticulum stress from protein aggregation, and mitochondrial calcium transport [23,24,25,26]. The remaining 90% of PD cases are typically classified as sporadic, which are believed to be caused by a combination of multiple etiological factors, including oxidative stress, and adverse and harmful environmental factors that are not fully understood [27].…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal or ineffective cellular responses to mTOR inhibitors may be due to activation of cytoprotective pathways including autophagic flux [9,30,31,47]. We now demonstrate that the autophagic flux inhibitor (HCQ) alters LD abundance in both malignant and normal renal cell lines (Fig 5C).…”
Section: Plos Onementioning
confidence: 63%